Effects of Intermittent Pneumatic Calf Compression On Postoperative Thrombin and Plasmin Activity - Weitz, Jeffrey; Michelsen, Jost; Gold, Kenneth; Owen, John; Carpenter, Duncan (Thrombosis and Haemostasis, 1986)
A previous study of neurosurgical patients demonstrated an imbalance between thrombin and plasmin action following surgery. The present study was designed to determine the effect of intermittent pneumatic calf compression on postoperative enzyme activity. Fibrinopeptide A (FPA) and Bβ 1-42 levels, reflecting thrombin and plasmin action respectively, were measured daily in patients undergoing elective craniotomy. Two of 9 patients not receiving calf compression developed positive fibrinogen leg scans, while none of 5 patients receiving prophylaxis had positive scans. Calf compression was associated with a markedly altered pattern of changes in the fibrinopeptide values following surgery. Without compression, there was perturbation of the balance between thrombin and plasmin action on the day after surgery as reflected by an increase in the FPA/Bβ 1-42 ratio. In contrast, in those receiving prophylaxis there was no change in this ratio on the first postoperative day. Calf compression both blunted the mean postoperative increase in the FPA level (1.8 nM vs 4.7 nM; p <.05) and augmented the mean Bβ 1-42 value (3.0 nM vs 0.2 nM; p <.05) so that the mean increase in the FPA/ Bβ 1-42 ratio was only 0.1 with calf compression as compared to 2.2 without it (p <.05). Systemic modulation of both the coagulation and fibrinolytic pathways thus occurred in association with calf compression.
Keywords: Calf compression; Thrombin/plasmin activity